Peptidomics for discovery, bioavailability and monitoring of dairy bioactive peptides - Sánchez-Rivera, Laura; Martínez-Maqueda, Daniel; Cruz-Huerta, Elvia; Miralles, Beatriz; Recio, Isidra (Food research international, 2014)
In the last years, the identification and characterization of bioactive peptides have become emerging research subjects. Food peptidomics can be considered a subfield of the food proteomics focused on composition, interaction and properties of peptides present in a food matrix. On the basis of the description of recent works, the objective of this review is to highlight the increasing role of peptidomics as indispensable tool in the fields of discovery, bioavailability and monitoring of dairy bioactive peptides. The enhanced peptide identification, resulting from the valuable mass spectrometry development and the regular use of high-resolution techniques, supports the application of peptidomic approaches in the case of empirical bioactive peptide identification workflow. Bioinformatic-driven approaches have gradually gained importance through the wider application of in silico analysis, structure activity relationship models, chemometrics and peptide database management. Investigations of bioactive peptide modifications during digestion, whether it be selective or untargeted search using peptidomic tools have been discussed, as well as peptide changes along absorption, distribution, metabolism and elimination, including studies in cellular and animal models. Examples of application of peptidomics in the analysis of bioactive peptide occurrence in dairy products together with peptide monitoring during scaling up, industrial treatments and storage have been also described. •Peptidomics has an increasing role in the bioactive peptides field.•In the active peptide discovery mass spectrometry has become an undisputed technique.•Bioinformatic tools have gradually gained importance in peptidomics.•Determination of bioavailability is essential to demonstrate the elicited effects.